2016
DOI: 10.1016/j.scitotenv.2016.07.213
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the sources of nitrate and the microbiological sources of pollution in the Sava River Basin

Abstract: Coupled measurements of nitrate (NO), nitrogen (N), and oxygen (O) isotopic composition (δN and δO) were used to investigate the sources and processes of N cycling, while the microbial source tracking (MST) method was used to identify microbiological pollution in the surface water of the Sava River Basin (SRB) in autumn in 2014 and 2015 during high and low water discharge. Atmospheric nitrate deposition or nitrate-containing fertilizers were found not to be significant sources of riverine nitrate in the SRB. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(19 citation statements)
references
References 45 publications
2
16
0
1
Order By: Relevance
“…Nitrogen fertilization of the surrounding agricultural areas at the points studied, waste water, lost wells and livestock waste, the results achieved are similar to the conclusions reached by (Barakat et al,2016;Fetouani et al,2008;Lagnika et al, 2014;Nouayti et al, 2015;Matzeu et al, 2017;Vrzel et al, 2016), including animal excreta. The high nitrate levels sometimes correspond to the reduction of nitrates to nitrites by reducing aerobic bacteria, the same conclusions of which can be found in a study by (Heriarivony et al, 2016;Lamribah et al, 2013).…”
Section: Fig 3 Statistical Analysis Of Nitrate Results For the Foursupporting
confidence: 86%
“…Nitrogen fertilization of the surrounding agricultural areas at the points studied, waste water, lost wells and livestock waste, the results achieved are similar to the conclusions reached by (Barakat et al,2016;Fetouani et al,2008;Lagnika et al, 2014;Nouayti et al, 2015;Matzeu et al, 2017;Vrzel et al, 2016), including animal excreta. The high nitrate levels sometimes correspond to the reduction of nitrates to nitrites by reducing aerobic bacteria, the same conclusions of which can be found in a study by (Heriarivony et al, 2016;Lamribah et al, 2013).…”
Section: Fig 3 Statistical Analysis Of Nitrate Results For the Foursupporting
confidence: 86%
“…The corresponding concentrations are between 0.42 and 1.21 μg/L fo ammonium ions and between 0.35 and 0.87 μg/L for nitrate ions. Similar variations were observed in the Sava River Basin (China) (Huang et al, 2010) and River Seine (France) (Billen et al, 2001). Nitrogen concentrations brought by solid wastes are of the order of micrograms per liter, but the accumulation phenomenon of these small quantities in sediments can contribute to Min and Max flow rates at the control point chosen on the river 0.00 2.00 4.00 6.00 8.00 10.00 the resurgence of eutrophication which develops each year in the waters of the river during the dry period (Kotti et al, 2005;Fianko et al, 2010).…”
Section: Cases Of Ammonium ( ) and Nitrate ( )supporting
confidence: 81%
“…This was not confirmed entirely in the analysed catchments in Pomerania, however, an increase in N-NH + 4 concentration was observed from summer to winter in OS and G and also in all streams concentration of N-NO − 3 increased from autumn to winter. Investigations carried out on the river Sava flowing through Slovenia, Bosnia and Hercegovina and Serbia indicated that N-NO − 3 concentrations were highest in winter and lowest in summer due to intense uptake by phytoplankton (Vrzel et al, 2016). A similar tendency occurred in the Gulf of Gdansk (SATBALTYK, 2018).…”
Section: Discussionmentioning
confidence: 92%